Differences In Mathematic Problem Solving Ability and Creative Thinking Of Students Teached With Realistic Mathematic Education Learning Models and Problem Solving - Maisyaroh (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
This study aims to determine: 1)Differences in problem solving abilities and mathematical creative thinking of students who are taught using realistic mathematical education learning models and students who are taught using problem solving learning models; 2)Differences in mathematical problem solving abilities of students who are taught using realistic mathematical education learning models with students who are taught using problem solving learning models; 3)Differences in students' mathematical creative thinking abilities who are taught using realistic mathematical education learning models with students who are taught using problem solving learning models.This type of research is a quasi-experimental. The population in this study were all students of MAS Pondok Pesantren Darul Qur'an. The sample in this study was class XI IIK 1 as a class that was taught using a problem solving learning model and class X IIK 2 as a class that was taught using a realistic mathematical education learning model. The data were obtained from the post-test with 5 questions for the problem-solving ability test and 5 questions for the students' mathematical creative thinking ability. The data were analyzed descriptively and using the Two Way ANOVA technique and continued with the Tuckey test.Based on the results of data analysis and discussion, it is obtained: 1)There are differences in problem solving abilities and mathematical creative thinking of students who are taught using realistic mathematical education learning models with students who are taught using problem solving learning models; 2)There are differences in the mathematical problem solving abilities of students who are taught using a realistic mathematical education model with students who are taught using a problem solving learning model; 3)There are differences in the mathematical creative thinking ability of students who are taught using a realistic mathematical education model with students who are taught using a problem solving learning model.